Mental and emotional health impacts of vasa previa on birthing individuals and health care providers: a scoping review protocol - Aleksandra M. Zuk; Samara Green; Jordan A. Harry; Christina Godfrey; Graeme Smith; Maria Ospina; Shahirose Premji; Catherine Lindsay Goldie; Erna Snelgrove-Clarke; Amanda Ross-White; Maria P. Velez (JBI Evidence Synthesis, 2026)
Objective: This scoping review will assess mental and emotional outcomes of birthing individuals diagnosed with vasa previa (VP) in any birthing context, including evidence that captures the perspectives of health care providers involved in their care. Introduction: VP is a rare obstetric complication that poses a significant risk of perinatal morbidity and mortality. There is a limited understanding of the emotional and psychological impacts on birthing individuals diagnosed with VP. The review will explore mental or emotional health outcomes related to the diagnosis of VP and the care for birthing individuals with this diagnosis. Eligibility criteria: This review will include all birthing individuals diagnosed with VP, as well as health care providers involved in their care. Studies from any birthing context will be considered. All types of primary data will be considered, without language or date restrictions. Methods: The review will follow the JBI methodological framework using a 3-step search strategy: an initial limited search, a comprehensive database search, and screening of reference lists from included studies. Databases will include MEDLINE (Ovid), Embase (Ovid), CINAHL (EBSCOhost), PsycINFO (Ovid), Cochrane Central Register of Controlled Trials (CENTRAL), and the Maternity and Infant Care Database (EBSCOhost). Following a comprehensive search of all databases, titles and abstracts will be screened independently by 2 reviewers, with disagreements resolved by a third reviewer. Relevant studies will undergo full-text review. Data extraction will include study characteristics, participant demographics, and findings related to emotional and mental health outcomes. Evidence will be synthesized descriptively and narratively to map the extent and nature of existing evidence and identify knowledge gaps to inform future research. Review registration: Figshare https://doi.org/10.6084/m9.figshare.29648279.v4